1999
DOI: 10.1128/mcb.19.7.4806
|View full text |Cite
|
Sign up to set email alerts
|

Induced Focal Adhesion Kinase (FAK) Expression in FAK-Null Cells Enhances Cell Spreading and Migration Requiring Both Auto- and Activation Loop Phosphorylation Sites and Inhibits Adhesion-Dependent Tyrosine Phosphorylation of Pyk2

Abstract: Focal adhesion kinase (FAK) is a nonreceptor protein tyrosine kinase involved in integrin-mediated control of cell behavior. Following cell adhesion to components of the extracellular matrix, FAK becomes phosphorylated at multiple sites, including tyrosines 397, 576, and 577. Tyr-397 is an autophosphorylation site that promotes interaction with c-Src or Fyn. Tyr-576 and Tyr-577 lie in the putative activation loop of the kinase domain, and FAK catalytic activity may be elevated through phosphorylation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
355
4
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(392 citation statements)
references
References 79 publications
24
355
4
4
Order By: Relevance
“…This observation is not altogether novel: studies have shown that cells overexpressing FAK mutants incapable of binding paxillin exhibit the same phenotype [123]. Since FAK-null cells have also been documented to have more persistent adhesions and a reduced rate of migration when compared to reconstituted cells, we would suggest that with respect to adhesion dynamics, an inability of FAK to bind paxillin, is similar to a FAK-null phenotype [165]. Alternatively, the observation that the S250 phospho-isoform is present along peripheral actin stress fibres but absent from adhesions would suggest that this FAK-paxillin interaction takes place outside of the focal adhesion.…”
Section: Lmo4 In the Regulation Of This Complex (Unpublished)mentioning
confidence: 66%
“…This observation is not altogether novel: studies have shown that cells overexpressing FAK mutants incapable of binding paxillin exhibit the same phenotype [123]. Since FAK-null cells have also been documented to have more persistent adhesions and a reduced rate of migration when compared to reconstituted cells, we would suggest that with respect to adhesion dynamics, an inability of FAK to bind paxillin, is similar to a FAK-null phenotype [165]. Alternatively, the observation that the S250 phospho-isoform is present along peripheral actin stress fibres but absent from adhesions would suggest that this FAK-paxillin interaction takes place outside of the focal adhesion.…”
Section: Lmo4 In the Regulation Of This Complex (Unpublished)mentioning
confidence: 66%
“…As strategies using antisense oligonucleotides (Xu et al, 1996;Hauck et al, 2001) or RNA interference (RNAi) (Duxbury et al, 2003;Han et al, 2004) can reduce FAK expression in tumor cells, these methods have not yet been tested for specificity via FAK reconstitution and rescue assays. Only in RNAi-treated normal fibroblasts (Tilghman et al, 2005) and in reconstituted FAK-null (Owen et al, 1999;Sieg et al, 1999) or v-Src-transformed FAK-null fibroblasts (Hsia et al, 2003;Wu et al, 2005) have FAK re-expression and tyrosine phosphorylation been linked to the promotion of cell motility and/or invasion.…”
Section: Introductionmentioning
confidence: 99%
“…[6]. Subsequent Src-mediated phosphorylation of FAK at Tyr-576, Tyr-577, Tyr-861 and Try-925, is important for the maximal activation of FAK and phosphorylation at Tyr-397 [4,9,10]. This model of FAK activation and Tyr-397 phosphorylation is thought to be of central importance for FAKdependent signaling.…”
Section: Introductionmentioning
confidence: 99%
“…This model of FAK activation and Tyr-397 phosphorylation is thought to be of central importance for FAKdependent signaling. The biological importance of FAK-mediated signal transduction is underscored by the fact that this tyrosine kinase plays a fundamental role in embryonic development [11,12] and in the control of cell migration [9,[12][13][14][15][16][17][18][19], cell cycle progression [20] and apoptosis [21][22][23][24]. Furthermore, there is increasing evidence linking overexpression of FAK to the invasive properties of cancer cells [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%